Del esplendor a la ruina. De cómo la política liberal afectó a la orden de monjas dominicas de Santa Catalina de Siena de Morelia - Fonseca Ramírez, Cristina del Carmen (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
In my thesis I approached the convent of Dominican nuns of Santa Catalina de Siena during the eighteenth and part of the nineteenth century, focusing mainly on aspects of daily life and social role. At the end of this investigation there arose the concern to investigate thoroughly the life of the convent from the perspective of how it had been affected by liberal policies, from those applied by the Crown to those implemented by the liberal governments of the second half of the nineteenth century. From this perspective the contributions made by Gisela Von Wobeser in his book Colonial Domination, The Consolidation of Royal Vouchers, 1804-1812, were very useful for us to be able to understand much more broadly the problems raised by the implementation of the Consolidation of Valleys Reales not only in Michoacán but throughout the New-Hispanic territory. The sufficient information systematized by Gisela Von served as a reference to compare and better understand the data located in the archives of the Dominican nuns of Santa Catalina de Siena de Morelia. They were very important in the orientation I gave to my work, the contributions of Anne Staples mainly three texts: his doctoral thesis titled The tail of the devil in the conventual life.

En mi tesis de licenciatura abordé al convento de monjas dominicas de Santa Catalina de Siena durante el siglo XVIII y parte del siglo XIX, enfocándome sobre todo a aspectos de vida cotidiana y rol social. Al término de esta investigación surgió la inquietud de investigar a fondo la vida del convento desde la perspectiva de cómo había sido afectado por las políticas liberales, desde las aplicadas por la Corona hasta las implantadas por los gobiernos liberales de las segunda mitad del siglo XIX. Bajo esta perspectiva las contribuciones hechas por Gisela Von Wobeser en su libro Dominación Colonial, La Consolidación de Vales Reales, 1804 – 1812, nos fueron de gran utilidad para poder comprender de manera mucho más amplia la problemática suscitada con la implantación de la Consolidación de Vales Reales no sólo en Michoacán sino en todo el territorio novohispano. La basta información sistematizada por Gisela Von nos sirvió de referencia para comparar y entender mejor los datos localizados en el propio archivo de las monjas dominicas de Santa Catalina de Siena de Morelia. Fueron muy importantes en la orientación que di a mi trabajo, los aportes de Anne Staples sobre todo tres textos: su tesis doctoral titulada La cola del diablo en la vida conventual.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2006-0005; Opción en historia de México; Afectación; Política liberal; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2356